Comparative studies in electro-physical processes (ECM & EDM) for circular micro-holes drilling. (2018) - Rahman, M. Zishanur; Das, Alok Kumar; Chattopadhyaya, Somnath
Abstract: Day by day interest is growing in drilling of high quality and high aspect-ratio micro-holes in various difficult-to-cut materials for many applications. Electrochemical micro-drilling (ECMD) and electrodischarge micro-drilling (EDMD) are the two major electro-physical process (ECM and EDM) based cost-effective techniques, provide a better alternatives in drilling micro-holes with reasonably accurate dimensions and good surface finish in difficult-to-cut materials for various industrial applications especially in computer, electronic, and aerospace industries. This paper presents a review of comparative studies in electro-physical processes on the developments of circular micro-holes drilling. It highlights the studies on aspect-ratio, over-cut and diameter-error (difference between inlet diameter and exit diameter) of circular micro-holes obtained by various experiments of ECMD and EDMD. For further research, it will open up various challenging opportunities in the field of (i) development of micro-tools and micro-electrodes, and (ii) development in innovative techniques for the purpose of drilling high quality and high aspect ratio micro-holes into hard-to-machine materials using ECMD and EDMD..